2017
DOI: 10.1017/s0033291716003020
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical, pregnancy and socio-economic predictors for new-onset severe postpartum psychiatric disorders in primiparous women

Abstract: Background Childbirth is a potent trigger for the onset of psychiatric illness in women including postpartum depression (PPD) and postpartum psychosis (PP). Medical complications occurring during pregnancy and/or childbirth have been linked to postpartum psychiatric illness and sociodemographic factors. We evaluated if pregnancy and obstetrical predictors have similar effects on different types of postpartum psychiatric disorders. Method A population-based cohort study using Danish registers was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 91 publications
6
105
2
1
Order By: Relevance
“…This confirms our interpretation of the existing literature, which, though obfuscated by variation in methods and study populations, overall is more supportive of a forward causation, such that pre‐existing depression predisposes women to develop GDM, rather than the reverse. This is in line with the majority of relevant studies which also found no association of GDM with the later development of perinatal depression . In those studies where GDM was reported to precede depression , excessive maternal weight gain and Caesarean delivery may have been important mediating factors.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This confirms our interpretation of the existing literature, which, though obfuscated by variation in methods and study populations, overall is more supportive of a forward causation, such that pre‐existing depression predisposes women to develop GDM, rather than the reverse. This is in line with the majority of relevant studies which also found no association of GDM with the later development of perinatal depression . In those studies where GDM was reported to precede depression , excessive maternal weight gain and Caesarean delivery may have been important mediating factors.…”
Section: Discussionsupporting
confidence: 88%
“…In those studies where GDM was reported to precede depression , excessive maternal weight gain and Caesarean delivery may have been important mediating factors. Only a single study that we reviewed found an association between GDM and PPD that was robust to adjustments , and one other found such an association but was unable to conduct the relevant adjustments .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the above findings being in line with our observations, five other studies have found no associations between GDM and PPD/PPDS (Huang et al, 2015;Kim et al, 2005;Liu and Tronick, 2013;Meltzer-Brody et al, 2017;Miller et al, 2016). However, it is notable that the only one of these five studies to specify the diagnostic criteria for GDM used the two-step method recommended by the American Diabetes Association (Huang et al, 2015).…”
Section: Comparison With Previous Literaturesupporting
confidence: 79%
“…Thus, it remains uncertain whether it is possible to compare the longitudinal US study (Huang et al, 2015) with our study, considering the noticeable difference in the criteria used to diagnose GDM. However, one of the five studies with no observed association between GDM and PPD/PPDS found an association between GDM and the postpartum acute stress reaction (Meltzer-Brody et al, 2017). Moreover, one cross-sectional study examined the relationship between GDM and PPDS in two ethnically different populations: an association was observed among Qatari women, while no such association was observable among other Arab women (Burgut et al, 2013).…”
Section: Comparison With Previous Literaturementioning
confidence: 99%